2014
DOI: 10.1016/j.drugalcdep.2014.07.007
|View full text |Cite
|
Sign up to set email alerts
|

Hippocampal volume mediates the relationship between measures of pre-treatment cocaine use and within-treatment cocaine abstinence

Abstract: Background Data suggest that the amygdala and hippocampus contribute to cocaine seeking and use, particularly following exposure to cocaine-related cues and contexts. Furthermore, indices of pre-treatment cocaine-use severity have been shown to correlate with treatment outcome in cocaine-dependent patients. Methods The aim of this study was to assess the relationships between amygdalar and hippocampal volumes and cocaine use before and during treatment. High-resolution magnetic-resonance brain images were ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
1
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 79 publications
1
11
1
1
Order By: Relevance
“…The absence of this structure/function association in both cocaine-dependent subgroups suggests disease-associated processes may be driving the differences in pHp neural activity. Further, in contrast to a recent report by Xu et al (61), we did not observe a difference in hippocampal volume between relapsed and early remission individuals.…”
Section: Discussioncontrasting
confidence: 99%
“…The absence of this structure/function association in both cocaine-dependent subgroups suggests disease-associated processes may be driving the differences in pHp neural activity. Further, in contrast to a recent report by Xu et al (61), we did not observe a difference in hippocampal volume between relapsed and early remission individuals.…”
Section: Discussioncontrasting
confidence: 99%
“…The same group was able to replicate these predictive findings in an independent sample using the seed derived from their initial study and a measure of cerebral blood flow done with Single-photon emission computed tomography (SPECT, rather than pCASL) (Adinoff, Harris, Gu, & Stein, 2016). This proposed hippocampal hyperactivity supports other work in which hippocampal volume was positively associated with a return to drug use (Xu et al, 2014). …”
Section: Section 3: Predicting Relapsesupporting
confidence: 90%
“…For instance, increased amygdala activation in response to implicit cocaine cues correlated with positive affective response ratings to the cues—demonstrating its importance in identification of salience of drug-related stimuli even outside of awareness. (Childress et al, 2008) Amygdala volume has been reported as smaller among cocaine-dependent people compared to controls (Makris et al, 2004) however more recent studies with larger sample sizes have found divergent results (Mei, Xu, Carroll, & Potenza, 2015; Xu et al, 2014). Despite no significant differences in volume, Mei et al did find a negative relationship in cocaine users between amygdala volume and measures of impulsivity (Mei et al, 2015).…”
Section: Section 2: Executive and Limbic System Irregularities In Cocmentioning
confidence: 99%
See 1 more Smart Citation
“…Neural structural factors within regions including the caudate and hippocapmus are related to treatment outcomes among individuals with addictions (Xu et al, 2014; Yip et al, 2014). In addition, individual variability in neurofunctional responses during MID task performance has been linked to neurostructural variability (Yip et al, 2015).…”
Section: Discussionmentioning
confidence: 99%